(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To survey some clinical and paraclinical characteristics of patients with periarthritis of the shoulder and evaluate the effectiveness of acupressure massage in reducing pain and restoring shoulder movement in patients at the Department of Traditional Medicine, Le Van Viet Hospital, Ho Chi Minh City. Subjects and research methods: Including patients with confirmed diagnosis of mitochondrial disease, who met the criteria for disease selection, agreed to participate in research and treatment at the Department of Traditional Medicine, Le Van Viet Hospital, Ho Chi Minh City from April 2021 to April 2022. Using clinical intervention research methods, comparing before and after treatment. Results: The average age of the study subjects was 56.7 ± 12.4, of which the age of 60 and older accounted for 39.2%. Females have a higher percentage than males, with 60.8% female and 39.2% male. The average pain score according to QDSA after 7 days of treatment decreased to 27.96 ± 3.89, after 14 days of treatment decreased to 17.12 ± 3.78. The average pain score according to VAS after 7 days of treatment decreased to 5.25 ± 0.98, after 14 days of treatment decreased to 2.71 ± 0.57. Shoulder flexion range, shoulder spread range, internal rotation range, and lateral rotation range have all improved. The patient’s basic function performance improves. After 14 days of treatment, the mild restriction group accounted for 66.7%, the moderate limit group accounted for 31.4%, there were no patients with severe limitation of shoulder movement when performing basic functions. Conclusion: Treatment of mitochondrial disease with massage has been shown to effectively reduce pain, improve shoulder range of motion, and improve the degree of limitation in performing daily activities. clinically undesirable use. Therefore, the massage method should be popularized and widely applied in medical facilities, depending on the actual local situation for the convenience of the patient.